Relationship of morphofunctional indicators with indicators of general physical training of mongolian wrestlers according to the results of multiple regression analysis - Shagdar Bat-Erdene,; Gundegmaa Lkhagvasuren, (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the relationship between morphofunctional indicators and indicators of general physical fitness of Mongolian athletes. Methods and structure of the study. The work analyzes the most important characteristics and indicators of the body condition (anthropometric data, body composition data, functional parameters) of highly qualified athletes, providing significant connections with physical fitness tests. To achieve this goal, 181 highly qualified athletes, mainly involved in martial arts, were examined. Results and conclusions. Based on the results of multiple regression analysis, morphofunctional models of the motor qualities of Mongolian highly qualified athletes were built, which are based on morphological characteristics, body composition indicators obtained using the bioimpedansometry method, and functional characteristics that can be used in sports selection, at the initial stage of preparation and at the stage of individualization sportsmanship in a long-term training process.